UPAYA PENINGKATAN KETERAMPILAN MENULIS MENGGUNAKAN MEDIA DIGITAL PADA SISWA KELAS 2 SDN TANAH KALI KEDINDING 1/251 SURABAYA - Oktavia, Devin Dwi; Budiyono, Budiyono; Ayuningtyas, Reny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to enhance the writing skills of second-grade students at SDN Tanah Kali Kedinding I/251 Surabaya using digital media. The problem identified is the students' difficulty in mastering basic writing skills, which is a crucial component of the educational curriculum. Digital media, including various tools and platforms such as educational apps, word processors, and interactive writing games, can serve as an effective medium for teaching writing.The research methodology employed is classroom action research (CAR) with a cyclical model consisting of planning, implementation, observation, and reflection. The subjects of this study are second-grade students. Data were collected through observations, interviews, and document analysis of students' written work before and after the application of digital media. The results indicate a significant improvement in students' writing skills after using digital media. This improvement is evident in the organization of ideas, the use of more varied vocabulary, and technical writing abilities. Additionally, students demonstrated higher learning motivation and a positive attitude towards writing lessons. In conclusion, the use of digital media can be an effective strategy to enhance students' writing skills. Educators are encouraged to creatively and interactively use various digital platforms to support the learning process. Further (Linlin Hu, 2020)their impact on other aspects of language skills.